Effect of shaking on the improvement of aroma quality and transformation of volatile metabolites in black tea - Jinjin Wang; Wen Ouyang; Xizhe Zhu; Yongwen Jiang; Yaya Yu; Ming Chen; Haibo Yuan; Jinjie Hua (Food Chemistry: X, 2023)
Shaking is an innovative technology employed in black tea processing to enhance flavor. However, the effects of shaking on the evolutionary mechanisms of volatile metabolites (VMs) remain unclear. In this study, we compared the effects of a shaking–withering method with those of traditional withering on the flavor and VMs transformation of black tea. The results showed that black tea treated with shaking exhibited excellent quality with floral and fruity aroma. Based on gas chromatography-tandem mass spectrometry, 128 VMs (eight categories) were detected. Combining variable importance projection with odor activity value analysis, eight key differential VMs were identified. Shaking could promote the oxidative degradation of fatty acids and carotenoids and modulate the biosynthesis of terpenoids to facilitate the formation of floral/fruity VMs (such as (Z)-hexanoic acid-3-hexenyl ester, ethyl hexanoate, trans-β-ionone, and decanal). Our findings provide theoretical guidance for the production of high-quality black tea with floral and fruity aromas.